Analysis of the Determinants of Preeclampsia in Samarinda City - Febriana Metallica Yeng Heling; Cipta Pramana; Nurhayati Nurhayati (Rifa'Institute, 2026)
Introduction: Preeclampsia remains one of the leading causes of maternal morbidity and mortality worldwide and contributes substantially to adverse maternal and fetal outcomes. Objective: This study aimed to analyze determinants of preeclampsia among pregnant women in Samarinda City, Indonesia. Method: A quantitative analytical observational study with a retrospective case-control design was conducted using secondary maternal health data from 11 community health centers in Samarinda City during 2023-2024. The study included 246 respondents consisting of 82 cases of preeclampsia and 164 controls. Independent variables included maternal age, pre-pregnancy body mass index, parity, and pregnancy interval. Data were analyzed using univariate analysis, Chi-square tests for bivariate analysis, and binary logistic regression for multivariable analysis. Result and Discussion: Bivariate analysis showed that pre-pregnancy body mass index was significantly associated with preeclampsia, while maternal age, parity, and pregnancy interval were not statistically significant. Multivariable logistic regression demonstrated that pre-pregnancy body mass index was the strongest determinant of preeclampsia, with women who were overweight or obese before pregnancy having 3.621 times higher odds of developing preeclampsia than women with normal body mass index. Maternal age younger than 20 years or older than 35 years was also independently associated with an increased risk of preeclampsia, whereas parity and pregnancy interval were not significantly associated after adjustment. These findings show the importance of maternal nutritional status and reproductive age in the occurrence of preeclampsia. Conclusions: Pre-pregnancy body mass index was the most dominant determinant of preeclampsia among the variables examined, followed by maternal age, while parity and pregnancy interval were not significantly associated with preeclampsia among pregnant women in Samarinda City